Chronic Periaortitis (Retroperitoneal Fibrosis) Concurrent with Recurrent Cutaneous Eosinophilic Vasculitis - Despoina Kiorpelidou; Georgios Gaitanis; Aikaterini Zioga; Athina C. Tsili; Ioannis D. Bassukas (Case Reports in Dermatological Medicine)
Chronic periaortitis (CP) is usually accompanied by at least mild manifestations of systemic autoimmunity; however, skin manifestations are rare. Here, we report an 82-year-old woman presenting with a pruritic annular eosinophilic dermatosis that led to the diagnosis of recurrent cutaneous eosinophilic vasculitis (RCEV) coexisting with a latent CP. The present paper is reminder that a CP should be included as a potential differential diagnosis in the elaboration of patients with cutaneous vasculitis that is suspicious of underlying autoimmunity.